Aplicador dinâmico de herbicida e sensoriamento de altura: estratégias de automação para a roçadeira química Campo Limpo - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This applied computing study analyzes and proposes improvements for operation of the Campo Limpo selective applicator for agrochemicals, a device that promotes weed control by the contact of wet ropes with herbicide on weeds. The main objective is to improve application technology by dynamically controlling the herbicide flow as a function of speed and weed infestation density. The first phase of the research aimed to automate the measure of weed height using low-cost sensors. Documentation of research performance activities can be found in annexes presented as a technical report. A new autonomous device was prototyped to carry out experimental activities. In conjunction with theoretical studies the prototype consolidated the relationship between sensors and environment, allowing to evaluate the efficiency of sensors in detecting the height of weeds. The preliminary results demonstrated the feasibility of identifying invasive plants height using low-cost distance sensors, specifically the ToF laser sensor VL53L1X and the TFmini Plus, together with the ultrasonic sensor HC-SR04. The dynamic and self-regulated application of herbicide considering different application scenarios and the improvements in the sensor module, allowed the correct positioning of herbicides applicators and the stabilization of the amount of herbicide applied per area. However, volume applied in the first automated system operation was lower than expected requiring a new experimental procedure. Using data stored and computing simulation causes of lower volume of application were identified allowing the calibration of the equipment as desired.
Keywords: Sensoriamento de pastagem; Pecuária de precisão; Controle de plantas daninhas; Recuperação de pastagens; Pasture sensing; Precision agriculture; Weed control; Pasture restoration; CNPQ::ENGENHARIAS